The safety of combining Endostar with concurrent chemoradiotherapy for the treatment of locally advanced cervical cancer and the evaluation of its anti-angiogenic effects via transrectal contrast-enhanced ultrasound - Wu, Fang; Lu, Zhouxue; Que, Jinting; Ma, Shanshan; Jiang, Li; Tang, Xiaobi; Zheng, Chengshan; Zhou, Li; Huang, Qiufeng; Zhang, Yong (Frontiers in Oncology, 2025)
BackgroundIn recent years, exploring the addition of angiogenesis inhibitors to chemoradiotherapy for locally advanced cervical cancer (LACC) has gained research interest. This study assessed the safety and anti-angiogenic effects of combining Endostar with concurrent chemoradiotherapy (CCRT) via transrectal contrast-enhanced ultrasound.MethodsA total of 120 patients with locally advanced cervical cancer (LACC) were randomly allocated to two groups: CCRT combined with Endostar (CRT+E group, n = 60) and CCRT alone (CRT group, n = 60). Endostar was administered intravenously before radiotherapy and repeated for four cycles. All patients received platinum-based CCRT. Adverse events were monitored, and transrectal contrast-enhanced ultrasonography (CEUS) was conducted before, during, and after radiotherapy. Vascular malformation (VM) rates were calculated from tumor cross-sectional images, and quantitative analysis software measured peak intensity (PI), time to peak (TTP), and mean transit time (MTT) of tumor vessels.ResultsNo significant differences were observed in hematological, hepatic, renal, gastrointestinal, or cardiac adverse reactions between the two groups (all P>0.05). In the CRT+E group, VM rates, TTP, and MTT significantly differed at three time points (with P values of 0.003, 0.002, and P<0.001, respectively), whereas the CRT group showed no significant changes (all P>0.05). Post-radiotherapy, statistically significant differences emerged between the CRT+E and CRT groups for VM rates (P = 0.027), MTT (P = 0.027), and TTP (P < 0.001), while PI showed no significant difference (65.67 ± 36.53 vs. 74.69 ± 61.21, P = 0.598).ConclusionThe combination of Endostar with CCRT for locally advanced cervical cancer (LACC) demonstrated favorable safety and tolerability. Transrectal contrast-enhanced ultrasound (CEUS) effectively assessed tumor vascular normalization induced by Endostar during CCRT. Specifically, Endostar significantly reduced VM rates and shortened MTT, suggesting its potential to normalize tumor vasculature.